Advanced age woman with diminished ovarian reserve obtained live birth following a zero pronuclei-derived four-cell frozen-thawed embryo transfer on day 4: a case report - Zhang, Xiao-lei; Chen, Yong-qian; Zhang, Ya-juan (Frontiers in Medicine, 2024)
Objective: Advanced maternal age and diminished ovarian reserve (DOR) are challenges in infertile patients for in vitro fertilization-embryo transfer (IVF-ET).This study aimed to investigate the pregnancy outcomes of women with advanced age and DOR undergoing low-quality embryo transfers.Case report: We report a rare case of successful pregnancy resulting from a zero pronuclei (0PN)-derived four-cell embryo transfer on day 4 (D4). An advanced age patient with diminished ovarian reserve (DOR) underwent five unsuccessful embryo transfers. A successful outcome was achieved when the patient underwent a hormone replacement FET cycle and received 0PN-derived four-cell frozen-thawed cleavage embryo transfer on D4. Fourteen days after the transfer, her serum hCG level was 575.3 mIU/ml. Subsequent prenatal examinations were normal, and the patient delivered a full-term healthy baby girl by caesarean section. Achieving a successful pregnancy after 0PN-derived four-cell frozen-thawed embryo transfer on D4 is rare. This increasingly exhibits significance for advanced age patients with DOR.Selectively transferring embryos with slow growth but low fragments and no evident damage is beneficial for advanced age patients with DOR. For these individuals, obtaining embryos is challenging. Therefore, a personalized embryo transfer strategy should be considered to increase the possibility of pregnancy.